Dystocia due to Hydrocephalic Monster in a Chihuahua Dog - Ruthrakumar, Ravichandran; Vinayaga, Senthil Kumar Jawahar; Gopikrishnan, Duraisamy; Palanismy, Mahakrishnan; Devadharshini, Nagaladi Periyasamy; Gopal, Kuppusamy; Selvaraju, Mani (The Indian Journal of Animal Reproduction, 2024)
The incidence of dystocia in companion animals is relatively low compared to other farm animals, however when dystocia  occurs it needs immediate intervention. The present report is a case about successful management of caesarean section in  a Chihuahua dog that suffered from dystocia due to fetal hydrocephalus.
Keywords: Dystocia; Hydrocephalus; Chihuahua; Dog